Emerging Place of JAK Inhibitors in the Treatment of Inborn Errors of Immunity - Hadjadj, Jérôme; Frémond, Marie-Louise; Neven, Bénédicte (Frontiers in Immunology, 2021)
Among inborn errors of immunity (IEI) some conditions are characterized by inflammation and autoimmunity at the front line and are particularly challenging to treat. Monogenic diseases associated with gain of function mutations in genes critical for cytokines signaling through the JAK/STAT pathway belong to this group. These conditions represent good candidates for treatment with JAK inhibitors. Type I interferonopathies, a group of recently identified monogenic autoinflammatory diseases characterized by excessive secretion of type I IFN are also good candidates with growing experiences reported in the literature. However, many questions remain regarding the choice of the drug, the dose (in particular in children), the efficacy on the various manifestations, the monitoring of the treatment, the management of potent side effects in particular in patients with infectious susceptibility. This review will summarize the current experiences reported and will highlight the unmet needs.